ANALISIS EPITEMOLOGI GURU PENDIDIKAN PANCASILA DAN KEWARGANEGARAAN DALAM KONTEKS PEMBELAJARAAN ONLINE: STUDI DI SMPN 1 MATARAM - I Nengah Arisudhana Widnyana; M. Afkar Mahendra; Wafiq Azizatun Munawarroh; Baiq Tiara Putri Fajriati; Olivia; Danu Dzulhakim; Edy Herianto (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The purpose of this study was to assess the role of epistemology in the teaching methods of Pancasila and Citizenship Education teachers at SMPN 1 MATARAM. The research used in this study is a qualitative descriptive method. There are three techniques used in the information collection process, namely interviews, observations, and documentation. The subjects of the study were PPKN teachers at SMPN 1 MATARAM. The results of the study show that the epistemology of Pancasila and Citizenship Education teachers in the context of online learning at this school consists of several aspects, namely: (1) The Impact of Teachers' Epistemological Understanding on the Effectiveness of Online Learning at SMPN 1 Mataram in the Context of Pancasila and Citizenship Education, (2) The Significance of Teachers' Epistemological Understanding in Developing Online Learning Methods that are Responsive to Changes in the Digital Era, (3) The Role of Teachers' Epistemology in Pancasila and Citizenship Education in the Context of Online Learning.